Oxidation of d‐Glucose to Glucaric Acid Using Au/C Catalysts. Issue 14 (8th June 2017) - Solmi, Stefania; Morreale, Calogero; Ospitali, Francesca; Agnoli, Stefano; Cavani, Fabrizio
Abstract: The reactivity of Au and AuBi nanoparticles supported on activated carbon AC was investigated in the direct oxidation of glucose to glucaric acid. The catalysts were very active, regardless of the Au nanoparticles size, but the catalyst with the smallest average particle diameter was the least selective to glucaric acid because of the enhanced consecutive oxidative degradation of the intermediately formed gluconic acid. The reaction network included the fast oxidation of glucose to gluconic acid, which was the only primary product, and its consecutive oxidation into either glucaric acid or lighter mono and dicarboxylic acids. The best glucaric acid yield obtained with a AuBi/AC catalyst (Au/Bi 3:1) was 31 %, with 18 % residual gluconic acid. The control of reaction parameters was essential to achieving the best selectivity. Specifically, the glucose concentration turned out to be a critical parameter in relation to O2 pressure and to glucose/metal ratio. Abstract : From wood to polymers with gold : Carbon‐supported gold nanoparticles are highly active in the direct oxidation of glucose to glucaric acid, an intermediate in the synthesis of biobased adipic acid. The catalyst outperforms Pt/C catalysts in both glucose/metal ratio and reaction conditions.